Cooling control of thermally-induced thermal runaway in 18, 650 lithium ion battery with water mist. (1st November 2019) - Liu, Tong; Liu, Yangpeng; Wang, Xishi; Kong, Xiangxiao; Li, Guochun
Highlights: Cooling control capacity of water mist on thermal runaway is studied. Effects of the states of charge on cooling process are investigated. State of charge of battery significantly impacts cooling efficiency of water mist. The conservative critical temperature for water mist release is about 186.5 °C. Results might be valuable for thermal runaway control of lithium ion batteries. Abstract: Lithium ion battery (LIB) thermal runaway (TR) has always been a potential risk that could result in serious damage. This likelihood has increased owing to the widespread application of LIBs, particularly in the electric-vehicle industry. Therefore, an effective method must be determined to prevent or mitigate this hazardous process. As a clean and efficient cooling technique, the effect of water mist (WM) on TR has been investigated through a series of tests in this study. Batteries with various states of charge (SOC) were heated with an electric heater to induce TR, and the surface temperatures were measured throughout the tests. The results show that TR can be controlled when the WM is released before the critical temperature is reached; the threshold temperature is at least 20 °C lower than the temperature of the TR onset. The determined conservative temperature for the WM application is 186.5 °C. At 25% SOC, the critical WM cooling rate is 1.87 times that of the critical heating rate. The value increases to 4.98 at 100% SOC, thereby indicating the increasing suppression difficulty with increasing SOC. Above the critical temperature, the TR is unstoppable. However, the maximal surface temperature can be controlled at values approximately 300 °C lower than those of the cases without WM. This is beneficial for the prevention of the TR propagation. TR can still be a potential risk for suppressed batteries. Nevertheless, the thermal hazard is mitigated with increasing onset temperature and a longer heating process. This study can contribute significant results for the control of TR in practice.